Strategi Pelaksanaan Mutu, Dan Pengawasan Mutu Yang Dilaksanakan Di SDN 105429 Desa Bajaronggi - Suwandi, Suwandi (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
ABSTRACT School quality management. The three schools / madrasah quality assurance process is constrained by human resources, but the budget for quality improvement must still be implemented if it is not implemented it will have a comprehensive impact on quality improvement factors in other components to improve the quality of school performance. implementation of school quality management. This study uses descriptive qualitative research where the researcher wants to know more about the research subject. The results of this study that the school is responsible for managing itself related to administrative, financial, and school personnel issues. First, it becomes a burden for some educators and education personnel to assign duties, responsibilities, authority and qualifications for each person to the related SPM. and influencing one another so that the implementation of MSS implementation can run effectively. Monitoring implementation. SDN 105429 Desa Bajaronggi always by WMM and wakasek to ensure that the system has been running effectively. If problems and discrepancies are found in the implementation, the system is reviewed and repaired immediately, so that the impact does not get wider. the implementation of evaluation and monitoring is carried out by the WPN jointly by the WPN by the unit or field periodically. Keywords: Quality Implementation, Quality Control